Potency Analysis of Mesenchymal Stromal Cells Using a Phospho‐STAT Matrix Loop Analytical Approach. (3rd June 2019) - Chinnadurai, Raghavan; Rajakumar, Augustine; Schneider, Andrew J.; Bushman, Wade A.; Hematti, Peiman; Galipeau, Jacques
Abstract: Potency assays for mesenchymal stromal cells (MSCs) need to be defined in advanced clinical trials. Here, we have developed an assay matrix approach that captures the signal transducer and activator of transcription (STAT) phosphorylation of MSCs upon stimulation with their combined secretome that arose with the interaction of activated peripheral blood mononuclear cells (PBMCs). Secretome of heat‐inactivated (HI) MSCs cocultured with and without activated PBMCs was used as an internal reference. We have compared the short‐term phosphorylation status of STAT1, STAT3, STAT4, STAT5, and STAT6 on MSCs derived from human bone marrow, adipose tissue, and umbilical cord using phosflow technology. Secretome of live MSCs cocultured with activated PBMCs downregulate STAT1 and STAT3 phosphorylation on MSCs, whereas the secretome of HI‐MSCs or PBMCs do not. Thus, investigation of the combined secretome of MSC and PBMC interaction on MSCs determine the potency of MSCs as the generator and sensor of the secretome. Bone marrow, adipose, and umbilical cord MSCs are comparable in modulating STAT1 and STAT3 responses. Measurements of STAT1 and STAT3 phosphorylation on MSCs as responder cells correlate and predict allogeneic T‐cell suppression. Our comparative phosphomatrix approach between live and reference HI‐MSCs defines the potency of MSCs as both stimulators and responders as part of a robust platform for predictive potency analysis.Stem Cells 2019;37:1119–1125 Abstract : We have demonstrated a potency testing approach using mesenchymal stromal cells as the stimulator and sensor of the secretome upon interaction with peripheral blood mononuclear cells. Heat inactivated mesenchymal stromal cells serve as the reference control for live mesenchymal stromal cells in this loop analytical approach.